Neutronic investigation of the Fuji-12 MSR reactor with a rectangular core configuration and plutonium-based fuel - Syarifah, Ratna Dewi; Mabruri, Ahmad Muzaki; Hanifah, Zein; Prasetya, Fajri; Arkundato, Artoto; Rohman, Lutfi; Maulina, Wenny (Penerbit Universiti Kebangsaan Malaysia, 2025)
A neutronic investigation of the design of the FUJI-12 Molten Salt Reactor (MSR) with a rectangular core configuration and plutonium-based fuel has been conducted. MSR FUJI-12 is a reactor with molten salt fuel developed by Japan. This reactor operates at a power of 350 MWt, an operating temperature of up to 980 K, and the capability to perform nuclide transmutation. The purpose of this research was to investigate the optimal design of the MSR FUJI-12 with a rectangular fuel channel lattice and plutonium-based fuel to achieve a neutronically safe design capable of burning the remaining reactor-grade plutonium (RGP) and weapon-grade plutonium (WGP) during reactor operation. In this research, the fuel composition is based on fluoride salt LiF-BeF2-ThF4-UF4-PuF3. The investigation was conducted using OpenMC neutronics code with the nuclear data library ENDF/B-VII.1. The results show that the optimal composition for RGP is 1.14% PuF3 and 0.60% PuF3 for RGP. In addition, the burn-up ratio of Pu239 in RGP is 44.3% and 61.1% for WGP. The results of the FIR analysis show that the WGP and RGP cause a very significant reduction in plutonium because the cleavage process is dominated by fissile plutonium. In addition, the changes in PuF3 composition in WGP and RGP affect the neutron reaction characteristics, including macroscopic cross-section, neutron spectrum flux, total reaction rate, neutron flux, and power distribution in axial and radial directions.